2022
DOI: 10.1038/s41375-022-01700-3
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-specific mutational landscape of clonal hematopoiesis

Abstract: Clonal hematopoiesis (CH) is characterized by somatic mutations in blood cells of individuals without hematologic disease. While the mutational landscape of CH in peripheral blood (PB) has been well characterized, detailed analyses addressing its spatial and cellular distribution in the bone marrow (BM) compartment are sparse. We studied CH driver mutations in healthy individuals (n = 261) across different anatomical and cellular compartments. Variant allele frequencies were higher in BM than PB and positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Next, we investigated the allelic burden of 18 different mutations from 14 patients (7 DNMT3A , 3 ASXL1 , 3 PPM1D , 2 TET2 , 2 CHEK2 , and 1 SF3B1 mutations) in flow‐sorted cell fractions. VAFs were significantly lower in B and T cells compared with monocytes and granulocytes consistent with previous findings 4 , 28 , 29 (Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…Next, we investigated the allelic burden of 18 different mutations from 14 patients (7 DNMT3A , 3 ASXL1 , 3 PPM1D , 2 TET2 , 2 CHEK2 , and 1 SF3B1 mutations) in flow‐sorted cell fractions. VAFs were significantly lower in B and T cells compared with monocytes and granulocytes consistent with previous findings 4 , 28 , 29 (Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…However, in this specific case, the consistent differences between pathological samples (myeloid and lymphoid) and saliva during the WES indicated that the latter was at least largely uncontaminated. Rather, the novel SNVs that we identified, since they were mostly not proven to be cancerogenic, might be signs of clonal hemopoiesis rather than being associated with PMF development/progression [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to realize that our understanding of CH has broadened beyond these initial narrow definitions. First, by using sensitive methods to detect variants in myeloid driver genes at VAFs below the 2% threshold, CH can be detected in over half of persons ≥70 years [ 17 , 21 ]. Second, whole-exome sequencing approaches in large cohorts revealed that CH can also affect driver genes implicated in lymphoid neoplasia, thereby identifying lymphoid CH (L-CH) as a more rare cousin of myeloid (M)-CH [ 22 ].…”
Section: Defining and Detecting The Spectrum Of Chmentioning
confidence: 99%
“…CH may directly or indirectly influence the differentiation capacity and/or function of various hematopoietic cell types, including neutrophils, monocytes, monocyte-derived macrophages, NK cells, B and T cells, as well as other immune-modulatory cells contributing to the osteo-hematopoietic niche, such as megakaryocytes and osteoclasts [ 14 , 26 28 ]. Recent studies have shed light on the lineage involvement of the most frequently mutated “DTA” genes [ 21 , 29 , 30 ]. Across these studies, sorted T cells showed a significantly lower allelic burden of mutated “DTA” genes (i.e.…”
Section: Defining and Detecting The Spectrum Of Chmentioning
confidence: 99%
See 1 more Smart Citation